Children's perspective on color, smell and flavor of toothpaste - Sahil Choudhari; Deepa Gurunathan; A C Kanthaswamy (Wolters Kluwer Medknow Publications, 2020)
Introduction: The foundation for healthy permanent teeth in children and teenagers is laid during the first years of life. Poor diet, poor habits of food intake, and inadequate toothbrushing habits during the first 2 years of life have been shown in several studies to be related to tooth decay in children. The development of caries in primary teeth further increases the risk of developing caries in permanent teeth. Materials and Methods: A survey was conducted with 787 school children aged between 5 years and 12 years in Chennai city on their perspective of toothpaste color, smell, and flavor. Results: Of 787 children, 222 chose red as the color they want in their toothpaste whereas only 61 children preferred white as their toothpaste color. The survey showed that 50% of the children wanted their toothpaste to taste sweet, followed by minty (20%), sour (14%), and spicy (11%). When asked about what they would like their toothpaste to smell like, majority (41%) of children opted for fruity, followed by sweet (23%), minty (18%), and fragrant (16%). Conclusion: Based on the responses made by 787 children aged between 5 and 12 years, it can be concluded that children prefer red color, fruity smell, and sweet flavor.